Directors Who Emigrate: Luis Castillo Ledón and Alfonso Cravioto (Palimpsesto, 2020)
This work outlines the repercussion of two figures in the Mexican cultural ambient: Luis Castillo Ledón and Alfonso Cravioto. Both writers associated with Savia Moderna (1906). The provided historiographical background centers in the collaborations of these two characters in the magazine, but it also outlines their migrations, before and after of the enterprise, showing that their relevance in the cultural Mexican panorama exceeds the pages of this enterprise. That is to say, this essay problematizes the narrow conception that we have of these two writers and put over the table a new interpretation that will help to understand better their interventions.
Keywords: Ateneo; México; Literature; Intellectual; 20th century